An Analysis of China’s Proposal to Control and Centrally Manage the Internet - Dupont, Alan (Journal of Telecommunications and the Digital Economy, 2020)
Governments and telecommunications companies have invested heavily in measures designed to protect overall system security. But these measures may not be enough if China is successful in setting the rules and designing the architecture of a new internet, because the one-party state’s internet vision reflects authoritarian values that are diametrically opposed to ours. China has suggested a radical change to the way the internet functions to the International Telecommunications Union. This would bake authoritarianism into the architecture underpinning the web, giving state-run internet service providers granular control over citizens’ use. The authoritarian state’s ability to monitor and control undersea fibre optic cables is emerging as a major national security issue for Australia and other democracies. The world could split into two separate information worlds, one led by the US and the other by China. A Balkanised internet is not in Australia’s interest. We must engage with friends and allies to come up with a fit-for-purpose world wide web that is more efficient, secure, user friendly and compatible with democracy.